Laser Apicoectomy with ER:YAG and Bone Xenograft Bio-Oss Collagen®. A Case Report - Krastev, Bogdan Petrov (The Journal of Dentists, 2014)
Main problem in apicoectomy procedures is the choice of access and flap, which determines the prognosis of the affected tooth. An additional complication is the presence of chronic periodontitis and increased tooth mobility. In such cases it is important to maintain the free marginal tissues and to do minimal trauma. Aim: To show the possibilities of the Er:YAG laser for treatment of apical lesions in a tooth with chronic periodontitis. Materials and Methods: Patient age 35 with moderate to severe chronic periodontitis, and a persistent cyst at tooth 22 was examined. After performing nonsurgical periodontal treatment apicoectomy was scheduled. A semilunar flap with vertical incisions was elevated 3mm from the gingival margin with a blade. All other procedures were performed with the help of Er:YAG laser in modes (release incision, bone remodeling, granulation tissue ablation, apex cutting). No retrograde filling was done. The cyst cavity was filled with Bio-Oss collagen® (Geistlich®, USA). Results: In the post treatment period a flap dehiscence occurred due to: loose sutures, necrosis, infection. After a period of one year the X-ray showed complete bone filling of the defect with light lucidity at the sight of the dehiscence, which might be merited to the epithelial tissue proliferation towards the defect which resulted in forming bone with lesser density. After one year the tooth is preserved with mobility grade 1. Discussion: The apicoectomy technique performed with Er:YAG is reliable and kept the soft tissues intact and also the tooth in spite of the severity of the chronic periodontitis. The technique can be recommended in similar cases.